A STUDY OF INFERTILITY TREATMENT METHODS IN THE LIGHT OF IRANIAN JURISPRUDENTIAL LAWS - Seyed Nader Aghiliyan , Farahnaz Sahab Roshan , Shamim Pilevary (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Having a child is one of the pillars of maintaining a family in Iranian lifestyles, but unfortunately some couples can not get pregnant for various reasons, and this infertility and the desire to have a child becomes a nightmare in their lives. Nowadays, assisted reproductive techniques are a way to end this nightmare. By examining medical issues and jurisprudential and legal aspects? This path can be clarified to make the decision easier, safer and without hesitation for the couple. Inability of a couple to conceive after one year of sexual intercourse is called infertility. Inability to reproduce has various causes and does not always mean infertility or permanent inability to have children. Artificial insemination methods as a supportive factor today are placed next to infertile couples so that they too can taste the pleasant taste of having children. Although this technology has been used in most countries of the world for many years, but it has been limited to Iran since 1989. After medical examinations, if the couple has a problem, receiving donated sperm and donated embryo is recommended, and if the wife has a problem, depending on the type of rented uterus problem, donated egg and donated embryo are suggested as a solution. In this article, we intend to first examine infertility and its causes and treatment methods from a medical point of view, and then the jurisprudential issues of infertility treatment methods. The purpose of this study is to eliminate the blind spots and incomprehensible legal issues of infertility methods and the integration of medicine and jurisprudence to help this generation. Through field studies and conversations with infertile couples, satisfactory results have been obtained from the reproductive, and as a result, some of the challenges and unknowns in the minds of infertile.